2019
DOI: 10.3390/v11040330
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of an MHC Class I-Like/Innate-Like T Cell Immune Surveillance System in Host Defense against Ranavirus (Frog Virus 3) Infection

Abstract: Besides the central role of classical Major Histocompatibility Complex (MHC) class Ia-restricted conventional Cluster of Differentiation 8 (CD8) T cells in antiviral host immune response, the amphibian Xenopus laevis critically rely on MHC class I-like (mhc1b10.1.L or XNC10)-restricted innate-like (i)T cells (iVα6 T cells) to control infection by the ranavirus Frog virus 3 (FV3). To complement and extend our previous reverse genetic studies showing that iVα6 T cells are required for tadpole survival, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In adult Xenopus, the lack of Va6 iT cells resulted in a less effective antiviral response, such as delayed viral clearance and more FV3-induce kidney damage (113). In addition, transitory depletion of Va6 iT cells resulted in delayed interferon and cytokine genes responses and long-lasting negative inability to control FV3 infection in tadpoles, which further supported the important role of Va6 iT cells in Xenopus immune surveillance system (114). Although iT cells have been demonstrated in Xenopus and mammals (112,115), they are still unknown in A. davidianus.…”
Section: Adaptive Immune Response To Gsivmentioning
confidence: 72%
“…In adult Xenopus, the lack of Va6 iT cells resulted in a less effective antiviral response, such as delayed viral clearance and more FV3-induce kidney damage (113). In addition, transitory depletion of Va6 iT cells resulted in delayed interferon and cytokine genes responses and long-lasting negative inability to control FV3 infection in tadpoles, which further supported the important role of Va6 iT cells in Xenopus immune surveillance system (114). Although iT cells have been demonstrated in Xenopus and mammals (112,115), they are still unknown in A. davidianus.…”
Section: Adaptive Immune Response To Gsivmentioning
confidence: 72%
“…These data are consistent with previous findings that during Mm and FV3 infection, tadpoles develop a delayed and limited inflammatory response ( Tnf α ; , Ifn γ, and Il1 β gene upregulation) and have limited capacity to restrain pathogen dissemination ( 4 , 33 , 41 , 42 ). Evidence that tadpole T cells play a critical role in the host resistance against FV3 and Mm have been obtained by a reverse genetic approach (shRNA and CRISPR/Cas9) targeting the invariant Vα6-Jα1.43 (iVα6) restricted by nonclassical MHC1-UBA10.1.L for FV3 and Vα45-Jα1.14 TCR (iVα45) associated with MHC1-UBA4.L for Mm ( 4 , 13 , 16 , 43 , 44 ). Thus, it is possible that susceptibility to some pathogens in X. laevis tadpoles may in part be due to some hyporesponsiveness of their T cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In studies investigating gene expression post-FV3 infection, it was found that the expression of pro-inflammatory genes (TNF-α, IFN-γ and IL-1 β ) in tadpoles is delayed or less responsive in comparison to the adult frogs [33,70]. Additional studies in tadpoles also have revealed that the iT cell population with the TCR invariant V α 6 α 1.43 that is restricted by the nonclassical MHC-I molecule XNC10 plays an important role in the immune response against FV3 [104,105]. When XNC10 or iT V α 6 α 1.43 expression is silenced, the infected animals perish sooner [46,105].…”
Section: Pathogen Host Responsesmentioning
confidence: 99%